2022
DOI: 10.3389/fpsyg.2021.810559
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Among Teacher Emotional Intelligence, Work Engagement, Teacher Self-Efficacy, and Student Academic Achievement: A Moderated Mediation Model

Abstract: In recent years, many studies have been done to identify the factors that affect teacher emotions at schools. However, the empirical evidence on how teachers’ emotions influence students’ outcomes and performance is not extensive. Against this background, this study explored the correlation between teacher EI and student academic achievement and possible mechanisms may lie in this relationship. A sample of 365 Chinese teachers from 25 public middle schools participated in this study by completing measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 59 publications
4
37
0
3
Order By: Relevance
“…There was no significant difference in EI based on gender nor based on age which was measured through ANOVA. This is in line with the studies till far (Birol et al, 2009;S Jerslina and Dr. N Devaki, 2016;Wang, 2022). Nor there was any significant difference between teachers' seniority and their EI.…”
Section: Anovasupporting
confidence: 89%
“…There was no significant difference in EI based on gender nor based on age which was measured through ANOVA. This is in line with the studies till far (Birol et al, 2009;S Jerslina and Dr. N Devaki, 2016;Wang, 2022). Nor there was any significant difference between teachers' seniority and their EI.…”
Section: Anovasupporting
confidence: 89%
“…They argued that instructors’ self-efficacy is associated with teachers’ involvement in tasks, and teacher engagement is an indication for engaging in goal-iriented activities. In line with Granziera and Perera (2019) ; Wang (2021) also found that the attribute of self-efficacy can significantly influence the relationship between teacher engagement and learners’ academic success. He argued that self-efficacious instructors seem to regard instructional difficulties as a manageable issue and are inclined to employ innovative methodologies to contribute their learners to accomplishing their tasks.…”
Section: Review Of Literaturesupporting
confidence: 57%
“…A high teacher emotional competence contributes to the development of supportive teacher-student relationships, effective classroom management strategies, and successful emotional learning program implementation which in turn promote positive developmental outcomes in students’ achievements. Studies showed that high emotional intelligence is associated with high teachers’ classroom engagement [ 59 , 60 ] and contributes to an increase in student engagement [ 61 ] and student academic achievement [ 60 ]. Emotional intelligence plays a positive role in promoting students’ achievement by enhancing the effects of students’ self-perceptions of ability and self-esteem [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emotional intelligence plays a positive role in promoting students’ achievement by enhancing the effects of students’ self-perceptions of ability and self-esteem [ 62 ]. Studies found that emotional intelligence is a predictor of self-efficacy [ 60 , 63 , 64 , 65 ] and teacher effectiveness [ 20 , 61 , 63 , 65 , 66 , 67 , 68 ]. Furthermore, teachers’ age and experience were factors that impacted the association between emotional intelligence and organizational effectiveness in school circumstances [ 67 ].…”
Section: Discussionmentioning
confidence: 99%